Analisis Potensi Kebangkrutan Menggunakan Model Altman Z-Score, Springate S-Score Dan Zmijewski X-Score (Pada Perusahaan Sub Sektor Otomotif Yang Terdaftar Di Bursa Efek Indonesia periode 2016-2019) - Annisa Abidah Al-Rahma; M. Agus Salim; Achmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2021)
ABSTRACTThe purpose of this study is to determine the comparison results of Altman Z-Score, Springate S-Score and Zmijewski X-Score models, and to find out which prediction model is the most accurate prediction of potential bankruptcy in the automotive industry. The dependent variable used in this study is the probability of bankruptcy. In this study, the document data collection method obtained from www.idx.co.id was used. The sampling technique used is targeted sampling. The observation period is from 2016 to 2019. A total of 11 companies sampled. The analysis technology used is the Altman Z-Score, Springate S-Score and Zmijewski X-Score models as hypothesis testing tools, the accuracy level and error rate of which can determine the accuracy of the three models used. According to the analysis results of the Altman Z-Score, Springate S-Score and Zmijewski X-Score models of the automotive sub-industry companies listed on the Indonesian Stock Exchange from 2016 to 2019, the following conclusions can be drawn: The model can be used to predict potential bankruptcy. The most accurate model for predicting potential bankruptcies in the automotive sub-sector is the Zmijewski X-Score model, with an accuracy rate of 91%. Keywords: Bankruptcy, Altman Z score, Springate S score, Zmijewski X score